Peran Guru Sebagai Teladan Dalam Pendidikan Karakter Di Sulawesi Utara - Masinambow, Christo J. R.; Wakerkwa, Tori; Jacobus, Susan (Academy of Education Journal, 2025)
In the midst of the challenges of modernization and globalization, character education is an important component in forming students' personalities. Various problems, such as environmental influences and lack of special training on character education, make the teacher's role not optimal in instilling student character. This research aims to analyze the role of teachers in the character education process and provide recommendations for developing example-based educational practices. This research uses a qualitative method, a type of literature study. The research results show that teachers have a strategic role as role models in instilling positive characters, such as honesty, discipline, responsibility and tolerance. The teacher's example is reflected in daily behavior, interactions with students, and the application of values in the learning process. Thus, character education through teacher example is very effective in building positive attitudes in students. Additional support in the form of training, supportive policies, and collaboration between schools, parents and the community is needed to strengthen the role of teachers as role models in character education.